The Free Time Economy: Free Time Increase – by the Effect of the Adoption of "Intelligent Work" – as an Stimulating Factor for Internal Consumption - Cerbone, Pasquale (2016)
The following work is inserted in the discussion about the economic repercussions of the generation of more free time, due to the effect of “intelligent work”. The study intends to encourage a reflection on the need to abandon the old labor regimes, emphasizing in the economic advantages that this entails. The hypothesis on which this study is based is that more free time would generate greater internal consumption. Therefore, the introduction analyzes the state of the art on the subject of intelligent work, identified as a generator of free time, and shows successful cases as a result of its adoption. It also ponders on the importance of free time in the economy. The methodology adopted for field research is exploratory, descriptive and analytical methodology.